D‐dimer as a predictor of venous thromboembolism in acutely ill, hospitalized patients: a subanalysis of the randomized controlled MAGELLAN trial. (April 2014) - Cohen, A. T.; Spiro, T.E.; Spyropoulos, A. C.; DeSanctis, Y. H.; Homering, M.; Büller, H. R.; Haskell, L.; Hu, D.; Hull, R.; Mebazaa, A.; Merli, G.; Schellong, S.; et al.
Summary Background D‐dimer concentrations have not been evaluated extensively as a predictor of increased venous thromboembolism (VTE) risk in acutely ill, hospitalized medical patients. Objectives To analyze the relationships between D‐dimer concentration, VTE and bleeding in the MAGELLAN trial (NCT00571649). Patients/methods This was a multicenter, randomized, controlled trial. Patients aged ≥ 40 years, hospitalized for acute medical illnesses with risk factors for VTE received subcutaneous enoxaparin 40 mg once daily for 10 ± 4 days then placebo up to day 35, or oral rivaroxaban 10 mg once daily for 35 ± 4 days. Patients (n = 7581) were grouped by baseline D−dimer ≤ 2 × or > 2 × the upper limit of normal. VTE and major plus non‐major clinically relevant bleeding were recorded at day 10, day 35, and between days 11 and 35. Results The frequency of VTE was 3.5‐fold greater in patients with high D‐dimer concentrations. Multivariate analysis showed that D‐dimer was an independent predictor of the risk of VTE (odds ratio 2.29 [95% confidence interval 1.75–2.98]), and had a similar association to established risk factors for VTE, for example cancer and advanced age. In the high D‐dimer group, rivaroxaban was non‐inferior to enoxaparin at day 10 and, unlike the low D‐dimer group, superior to placebo at day 35 (P < 0.001) and days 11–35 (P < 0.001). In both groups, bleeding outcomes favored enoxaparin/placebo. Conclusions Elevated baseline D‐dimer concentrations may identify acutely ill, hospitalized medical patients at high risk of VTE for whom extended anticoagulant prophylaxis may provide greater benefit than for those with low D‐dimer concentrations.